Impact of blood salvage during liver transplantation on reduction in transfusion requirements - Sankarankutty,Ajith Kumar (2006)
PURPOSE: The aim of this study was to analyse the changes in transfusion requirements, in patients submitted to orthotopic liver transpantation from cadaveric donors, with the use of intraoperative red blood cell salvage (Cell Saver). METHODS: Data from 41 transplants were analysed. Intraoperative blood loss was calculated from the cell salvage, suction and the swabs. The autologous and heterologous transfusions were recorded The red blood salvage was performed using the Cell Saver 5 System (Haemonetics).. For analysis the patients were divided in two groups: one that used the Cell Saver and another that didn't. RESULTS: The median age of the patients was 50 years and the main indication for liver transplantation was cirrhosis (35 cases - 85.3%). The median blood loss was 8362 + 3994 ml (with the Cell Saver) and 10824 + 7002 ml (without the Cell Saver) and the median transfusion of heterologous packed red blood cells was 9,6 + 8 units (with the Cell Saver) compared to 22,3 + 21 units (without the Cell Saver). CONCLUSIONS: The Cells Saver has the potential to reduce the need for heterologous blood transfusion reducing the risks of transmissible diseases.